Finite element analysis for cooling of a vertical composite plate - Duranay, M; Inalli, M; Pihtili, K (Pergamon-Elsevier Science Ltd, 2000)
The composite materials often subject to the media having high and low temperatures. The temperature values of critical points on the materials must be known for this type of machine designing elements. In this study, the cooling problem of L-shaped composite vertical plate is investigated by theoretically and experimentally. The couples of steel-copper, steel-brass, brass-copper and steel-aluminum are selected for composite materials. The finite element method is used for the theoretical analysis. The transient temperature distribution for composite plates having different thickness is studied for various cooling media such as a stagnant air, a stagnant water, a stagnant oil or sprayed water. It is observed that the temperature increases on the contact points of the composite materials. Therefore, the thermal stress is the most important factor for the cooling process of the composite materials. (CV) 2000 Elsevier Science Ltd.